Work Motivation and Human Resource Management in Enhancing Lecturer Productivity at University of Dili - Manuela Oliveira De Carvalho Maia; Salustiano Piedade Dos Reis; Carla A,de J. da Costa (CV. Ulil Albab Corp, 2025)
The University of Dili (UNDIL) offers a wide range of academic programs in disciplines such as social sciences, engineering, and health sciences, aiming to produce qualified graduates who are competitive in the job market. This study investigates the influence of human resource development (HRD) and work motivation on lecturer productivity. Key HRD factors include training, promotion, recognition, health security, and participation in decision-making. The study involved all permanent lecturers at UNDIL (n = 130), using a census method. Descriptive analysis was conducted with SPSS, while structural relationships were tested using SmartPLS 4.0. The findings show that HRD does not have a significant direct effect on productivity (β = 0.291, T = 1.033, P = 0.302). However, work motivation significantly influences productivity and serves as a mediating factor between HRD and productivity. These results highlight that motivation—both intrinsic and extrinsic—is essential to translating HRD initiatives into improved academic performance, aligning with the university’s vision for quality education and institutional development.